ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION SKINCARE KOREA MAHASISWA KOTA BATAM - Renny Christiarini; Astri Rahmadilla (Journal of Global Business and Management Review, 2021)
Today, social media forms an increasingly central part of how companies communicate their marketing strategies to target consumers. In this study, the objective of this research is to identify the impacts and links that affect purchase intention as well as other variables, namely e-WOM, brand awareness, social media marketing, and brand image as intervening. The findings of a study conducted on 300 respondents who have buying interest in Korean skincare products indicate that it has a positive significant value of all variable X against variable Y. Based on the findings of this study indicate that there is a significant effect of the e-WOM variable, brand awareness, social media marketing, and brand image on variable Y, namely purchase intention.